Studi Perbandingan Penanganan Pengungsi Luar Negeri Di Indonesia, Australia, Dan Thailand - Mohamad Hidayat Muhtar; Zamroni Abdussamad; Zainal Abdul Aziz Hadju (Fakultas Hukum Universitas Islam Indonesia, 2023)
Indonesia specifically addresses the refugee issues in Presidential Regulation No. 125 of 2016 on the Handling of Foreign Refugees. The handling of refugee status in Indonesia is handed over to UNHCR considering that Indonesia is not a party to the 1951 Refugee Convention or the 1967 Protocol. Besides Indonesia, Australia and Thailand are also not parties to the convention. Therefore it is important to see a comparative study of policies between countries. This study also aims to find out whether Presidential Decree No. 125 of 2016 can resolve the problem of refugees in Indonesia and what is the policy comparison between Indonesia, Australia and Thailand. The research method used is normative legal research with a statutory approach. The results of the study concluded that Presidential Decree No. 125 of 2016 has adequately accommodated arrangements for overseas refugees, but there are still several provisions that have multiple interpretations, such as arrangements regarding